A proposed re-education programmed instruction in the use of two-word verbs for fourth year high school - Salvosa, Mercedes (Tayag) 1928- (s.n.], 1972)
The program materials found herein are designed to teach English two-word verbs to fourth year high school students. The program is based on a constructive analysis of English and Tagalog, which is a prerequisite in constructing effective instructional materials in second language teaching. Programmed materials were preceded with an Entry Behavior Test. Results show that the program works well with heterogeneously grouped students in fourth year high school. Each student could follow his own pace in the manipulation of the frames.